A Note on the Drazin Indices of Square Matrices. (10th February 2014) - Yu, Lijun; Bu, Tianyi; Zhou, Jiang
Abstract : For a square matrix A, the smallest nonnegative integer k such that rank (A k ) = rank (A k + 1 ) is called the Drazin index of A . In this paper, we give some results on the Drazin indices of sum and product of square matrices.